Technical Report Design Project 2-IBIO 3870 ECMOPlus (2018)
In Colombia, there are at least seven health care institutions who have an intensive care unit, where techniques of extracorporeal life support as artificial blood oxygenation through a membrane (ECMO) are of common practice. The Extracorporeal Life Support Organization (ELSO) is the entity responsible for the training and certification processes however, there are flaws in these processes that difficult preparing physicians for real-life situations. Consequently, physicians who use this procedure need support in the decision-making process to provide the best care they can to their patients. For this reason, ECMOPlus was created. A digital app that allows the medical personnel to complement the necessary information needed for an adequate intervention of an ECMO patient